First-time adoption of IAS 39 impact on selected Philippine universal banks - Salazar, Dani Rose C. (Philippine Management Review, 2006)
The adoption of IAS 39 (Financial Instruments : Recognition and Measurement) in the Philippines for fiscal year ended 2005 was felt most strongly by the banking sector. As of December 31 of that year, Philippine banks reported aggregate financial assets and financial liabilities of P7.1 trillion that are subject to the provisions of IAS 39. Using a sample that included the biggest universal banks in the country, this study finds that adoption of IAS 39 resulted in three main adjustments to the banks' financial condition and results of operations : 1) recognition of previously unrecognized assets and liabilities, (mainly derivative instruments); 2) re-measurement of existing assets and liabilities; and 3) reclassifications within asset accounts in the balance sheet. The net financial impact of these adjustments was a decrease of almost P15 billion in the sampled banks' reported assets, an increase of P650 million in their liabilities, and a decrease in their capital or equity of P15.53 billion. The decline in assets and capital arose principally from impairment losses recognized by the banks on their loans and receivables in compliance with IAS 39 measurement rules.